Consumer perceptions of third party product quality ratings - DE MAEYER, Peter (Institutional Knowledge at Singapore Management University, 2011)
Consumers increasingly rely on product quality information provided by third-party product ratings organizations. These organizations undertake the task of examining and testing competing products in the marketplace, establishing the level of quality associated with each product, and communicating this information to consumers. Despite the important role of product quality ratings in consumer decisions little research has been conducted to establish the factors which may influence consumer perceptions of these ratings. This paper examines the role of the information content provided by product quality ratings organizations on consumer perceptions. Furthermore, the influence of contextual variables, namely information cost, product category and advertising content, is examined. The results indicate that both content and context significantly influence consumer perceptions of source credibility and their intentions to use the product quality ratings in their purchase decisions.